THE ROLE OF ECONOMIC LAW IN MARKETING AND BRANDING REGULATION: ANALYSIS OF BUSINESS COMPETITION REGULATION, CONSUMER PROTECTION, AND INTELLECTUAL PROPERTY RIGHTS ON MARKET EFFICIENCY - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
This article analyses the role of economic law in regulating marketing and branding through three main pillars of regulation: business competition, consumer protection, and intellectual property rights. Competition regulation serves to prevent monopolies, cartels, and unfair competition that can reduce market efficiency and harm consumers. Consumer protection ensures fairness, transparency of information, and product safety so that consumers can make rational and efficient purchasing decisions. Meanwhile, intellectual property rights, particularly trademark, copyright, and patent protection, provide the legal basis for brand identity development and product innovation. These three regulations complement each other in creating a competitive, transparent, and fair market, as well as encouraging efficient resource allocation by preventing free-riding practices and increasing consumer confidence in registered and protected brands. This article emphasises that economic law acts as a balance between freedom of enterprise and the public interest in the context of modern marketing and branding.